Long-Term Prognosis of Quality of Life in Dogs Diagnosed With Mild to Moderate Elbow Dysplasia in Sweden - Bergström, Annika; Johard, Sofia; Lee, Marcel H.; Comin, Arianna (Frontiers in Veterinary Science, 2020)
Objective: The objective of this study was to increase knowledge regarding long term prognosis of mild to moderate elbow dysplasia (ED) using a canine orthopedic index. Study Design: Cross-sectional observational study. Sample Population: 60 dogs randomly selected from each of 5 different breeds and 3 ED groups: ED0 (control), ED1 and ED2 based on the Kennel Clubs screening results. The total number of selected dogs were 900 (60*5*3). Methods: Questionnaires were administered to owners by telephone-interview. Bayesian network modelling was used to assess the relation between ED grade, treatment options, dog demographics and quality of life indicators. Results: 765 questionnaires were collected (85% response rate), of which 61 concerned dogs euthanized due to osteoarthritis. There was no direct association between ED grade and owner’s perceived quality of life, but ED1 and ED2 dogs were more likely to receive veterinary care and subsequent NSAID treatment compared to ED0 dogs. A significant association was found between the occurrence of euthanasia due to orthopedic disease and ED scores 1 and 2 in the sample (p <0.001). Conclusion: The degree of osteoarthritis was not directly associated with the canine orthopedic index, except from ED2 and lameness score. It can be speculated that owners who paid closer attention to orthopaedic symptoms and perceived them as impairing their dogs’ lives were also more likely to seek veterinary care and get a treatment, irrespective of the ED grading.